The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s11092-006-5740-9
|View full text |Cite
|
Sign up to set email alerts
|

Parent Surveys for Teacher Evaluation

Abstract: Parent or guardian perceptions play a specialized role in the evaluation of school teachers. Parents are important stakeholders in teacher success, they are in some instances partners in the teachers' work, parents have unique personal information about student learning, and they can report on the teacher duties to inform parents about the classroom and child progress. This study analyzed the responses of parents to 12 survey items concerning teacher performance in 201 classrooms. The surveys were used as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Perhaps these extreme cases raise a lot of concern and involvement, which causes many people to discuss them. For example, Peterson et al (2003) found that parents are most concerned about inhumane treatment of students, lack of support for pupil learning, and ineffective communication and collaboration with parents. All these factors characterize incompetent teaching.…”
Section: Sources Of Informationmentioning
confidence: 99%
“…Perhaps these extreme cases raise a lot of concern and involvement, which causes many people to discuss them. For example, Peterson et al (2003) found that parents are most concerned about inhumane treatment of students, lack of support for pupil learning, and ineffective communication and collaboration with parents. All these factors characterize incompetent teaching.…”
Section: Sources Of Informationmentioning
confidence: 99%
“…Surveys can provide information on perceptions of teachers' practice by students, parents and others who may testify on teaching quality through their continuous interaction with the teacher (Peterson, 2000;Peterson et al, 2000Peterson et al, , 2003Jacob and Lefgren, 2005). Surveys collecting the views of students and parents are rarely used systematically in the context of formal frameworks for teacher appraisal.…”
Section: Surveys Of Students and Parentsmentioning
confidence: 99%
“…Student surveys are tools of teacher evaluation in Mexico, the Slovak Republic, Spain or Sweden, generally for teachers applying for a promotion; to our knowledge, there is no existing case in compulsory teacher evaluation schemes. While their utilisation can provide some interesting insights, cautions have to be taken because the evaluators are not teaching experts and do not necessarily value the same qualities than the ones which are supposed to enhance student learning (Peterson et al, 2000(Peterson et al, , 2003Jacob and Lefgren, 2005b). Research studies on the use or reliability of such procedures remain unfortunately very rare.…”
mentioning
confidence: 99%
“…They are less frequently direct evaluators, via questionnaires for example. The tiny current evidence on that subject shows that they value teacher characteristics that surprisingly depart from student achievement: 'the teacher's ability to promote student satisfaction' (Jacob and Lefgren, 2005b), 'humane treatment of students', 'support for pupil learning', and 'effective communication and collaboration with parents' (Peterson et al, 2003). Even if their perspective could be taken into account, their distance from the teaching professional standards, their ignorance about what happens in the classrooms, and their emotional implication suggest that their appraisals are far from sufficient for a comprehensive teacher evaluation scheme.…”
mentioning
confidence: 99%